Pengaruh Latar Belakang Pendidikan, Sistem Pengendalian Internal dan Pelatihan Akuntansi Terhadap Kualitas Laporan Keuangan pada BUMDes di Kecamatan Seririt - Darasanthi, Kadek Trisna; Julianto, I Putu; Vijaya, Diota Prameswari (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to examine the effect of educational background, internal control systems, and accounting training on the quality of financial statements of Village-Owned Enterprises (Badan Usaha Milik Desa or BUMDes) in Seririt Subdistrict. Using a quantitative causal-associative approach, the research involved 16 BUMDes units and 80 respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed with multiple linear regression. The findings reveal that: (1) the educational background of BUMDes managers has a significant positive impact on the quality of financial statements, (2) the implementation of internal control systems significantly enhances the reliability and accuracy of financial reporting, and (3) accounting training significantly improves financial reporting competence. These results suggest that strengthening internal controls, providing continuous accounting training, and ensuring competence-based recruitment are essential for improving BUMDes financial reporting quality. Furthermore, the study reinforces the relevance of contingency theory in accounting, indicating that the effectiveness of financial management depends on the alignment between internal organizational factors and external demands.